Determination of terminal competencies for graduating medical technology students - Aldave, Alicia A.
The study aimed to determine the terminal competencies of graduating medical technology students based on their professional roles and responsibilities as perceived by practicing medical technologists, researchers, laboratory administrators, pathologists and medical technology educators. The study reviewed secondary data and did task analysis to determine the minimum competencies of graduating medical technology students. Primary data were obtained from a rating scale instrument. Using a 115-item rating list of competencies drawn from the review of literature and task analysis, a preliminary survey was done on four practicing pathologists who are currently involved in medical technology education. They were asked to identify the professional role/s of medical technologists and rate each competency statements in order of importance: 4-very important, 3-important, 2-somewhat important, and 1-not important. Based on preliminary survey, all four respondents agreed that the professional roles of a medical technologist are that of being a laboratory diagnostician, educator, researcher and laboratory administrator/manager. Consequently, a 121-item rating list of competencies based on professional roles and responsibilities was developed. The actual survey of the 121-items final competency list was conducted in various laboratory hospitals and schools of medical technology in Metro Manila. The respondents of the study were chosen based on sampling criteria. They consisted of practicing medical technologists, laboratory administrators/managers, medical technology educators, pathologists and researchers. Out of one hundred twenty (120) questionnaires, only sixty two (62) were retrieved representing 51.67 percent response rate. Based on the response to the actual survey questionnaire, the most significant professional role of a medical technologist as perceived by majority of respondents was as laboratory diagnostician (95%). The other significant role of a medical technologist were that of an educator (82%), laboratory manager (74%) and researcher (71%). It is interesting to note that some medical technologist could perform a variety of tasks and assume a variety of roles. Frequency counts and percentages were used to determine the degree of agreement and disagreement on the competencies. The general research findings were processed and analyzed qualitatively and quantitatively. An overwhelming 124 out of 124 (100%) items on the competency list were considered important for a new graduate in the field of medical technology by majority of the respondents. Of 124 items, item #5 which refers to the ability of laboratory diagnostician to identify and label the clinical specimen correctly was the only single item rated very important by 100% of the respondents. A summary of the minimum list of terminal competencies for a graduating medical technology student was determined. Since, majority of the respondents rated the listed competencies as 4 and 3, a criterion level of 70% was arbitrarily set to distinguish those competencies which were considered very important and important. The respondents rated 64 out of 121 (51.61%) competencies as very important and 60 out of 121 (48.38%) competencies as important. Results of the study showed that while all the 124 items on competency list were perceived to be important by majority of respondents, students have many limitations in terms of teaching-learning opportunities as they are all under the supervision of medical technology staff and training officers. There is a strong need to provide more teaching-learning activities and curricular emphasis for the role of an educator, researcher and laboratory manager/administrator. The terminal competencies determined in this study could be used to develop the level competencies, intermediate competencies, review the course offerings, design training programs and formulate instructional designs for medical technology students.